2011
DOI: 10.1002/ird.614
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of modified DRAINMOD in predicting groundwater table fluctuations and yield of canola in paddy fields under snowy conditions (case study: Rasht Iran)

Abstract: The computer simulation hydrologic model, DRAINMOD and modified DRAINMOD (Luo et al., 2000) for cold condition, was used to predict the performance of surface drainage and yield of canola as post-rice cultivation during the wet growing season of [2004][2005] in Rasht, Iran.Performance of surface drainage system treatments with 2 m spacing and 15 cm drain depth as compared with plots having no drainage (4 Â 10 m 2 ), were used to evaluate the models. Evaluation of predicted daily groundwater table depths as com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 15 publications
2
9
0
Order By: Relevance
“…(2009) and Hassanpour et al . (2011). In the calibration system, the averages of daily simulated and measured NO 3 − ‐N concentrations were, respectively, 9.1 and 14.1 mg l −1 during three canola‐growing seasons.…”
Section: Resultsmentioning
confidence: 99%
“…(2009) and Hassanpour et al . (2011). In the calibration system, the averages of daily simulated and measured NO 3 − ‐N concentrations were, respectively, 9.1 and 14.1 mg l −1 during three canola‐growing seasons.…”
Section: Resultsmentioning
confidence: 99%
“…The current study has also revealed that relatively few studies report validation of waterlogging models; of those that did, DRAINMOD (Evans et al, 1991; Hardjoamidjojo & Skaggs, 1982; Hassanpour et al, 2011), APSIM‐Oryza, and GLAM‐WOFOST (Li et al, 2016) were adequate (RMSE between simulated and observed yield was 382 and 453 kg ha −1 , respectively); APSIM‐Soybean and APSIM‐Oryza fit the data well.…”
Section: Synthesis: Pathways Used To Model Waterloggingmentioning
confidence: 60%
“…The model described only 63% of the variation in observed corn yields for the 12‐year period. Hassanpour et al (2011) also reported an overestimation of simulated canola yield in evaluating the performance of surface drainage and canola crop growth in DRAINMOD. The discrepancy between predicted and measured yields in this case may be attributed to the empirical factors in Equation 3.…”
Section: Modeling Crop Waterloggingmentioning
confidence: 98%
See 1 more Smart Citation
“…This further facilitates to take proper decisions in case of complicated situations when collection of field information were both costly and laborious. The results of the DRAINMOD model performance in South Africa (Malota and Senzanje, 2015 and Sema Kale, 2011), Egypt (Neveen et al, 2013), Israel (Sanai and Jain, 2006), Iowa (Singh et al, 2006), Iran (Hassanpour et al, 2011, Samipour et al, 2010and Ebrahimian et al, 2010 and Iraq (Hamdi et al, 2006), confirmed that DRAINMOD can reliably imitate SSDS for various soils and weather situations. Further, it is also found from reviews that the DRAINMOD model is widely used model for design of SSDS under shallow water table conditions as reported by Prasher et al (1996) Malota and Senzanje (2015) reported the prediction of WTDs and drain discharges successfully through DRAINMOD in irrigated conditions.…”
Section: Introductionmentioning
confidence: 80%